P019 Is treatment response influenced by body mass index in juvenile idiopathic arthritis?. (March 2019) - Giani, T; Cimaz, R
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: There is evidence that obesity could be a risk factor for the severity and response to treatment in patients with RA due both to the mechanical effect of overweight and to the potential pro-inflammatory effects of cytokines produced by adipose tissue. Objectives: To evaluate the role of overweight and obesity in a cohort of patients with Juvenile Idiopathic Arthritis (JIA), in terms of incidence, disease activity, outcome and response to treatments. Methods: This single-center retrospective cohort study evaluated 110 children affected by JIA under treatment with anti-rheumatic agents (DMARDs, biologic agents). Changes from baseline in ESR, CRP, number of active joints, and BMI were analyzed under each treatment until last visit. BMI categories of 5–84th (normal weight), 85–94th (overweight), and ≥95th (obese) percentile were used. Patients with systemic JIA, uveitis, chronic comorbidities, or under other potentially confounding systemic treatments were excluded. Uni- and multivariate analyses were performed. Results: One hundred and ten JIA patients (polyarticular n=50, oligoarticular n=38, psoriatic n=12, enthesitis related arthritis n=8, undifferentiated n=2 ) were enrolled in the study, 75% girls, 25% boys. The mean age at treatment onset was 6.09 years. Baseline BMI was ≤84 th percentile in 80 patients, 85–94th in 27, and ≥95 th in 3. We did not observe a significant association between BMI and ESR, CRP, or number of active joints at baseline, while involvement of the joints of lower limbs was significantly greater (p=0.025) in overweight/obese patients. We observed a trend toward lower remission rates and higher number of relapses, both after DMARDs and biologics, in patients with higher BMI. Conclusions: This study focuses on the relationship between overweight/obesity and JIA. A significant correlation between obesity and a greater involvement of the joints of the lower limbs was observed at baseline. Furthermore our data suggest that obesity could negatively influence the course of the disease as well as treatment response. References: Marques A, Peralta M, Naia A, Loureiro N, de Matos MG. Prevalence of adult overweight and obesity in 20 European countries. Eur J Public Health 2018;28:295–300. Liu Y, Hazlewood GS, Kaplan GG, Eksteen B, Barnabe C. The impact of obesity on remission and disease activity in rheumatoid arthritis: a systematic review and meta-analysis. Arthritis Care Res (Hoboken) 2017;69:157–65. CF Pelajo, JM Lopez-Benitez, LC Miller. Obesity and disease activity in juvenile idiopathic arthritis. Pediatr Rheumatol 2012;10:3. Disclosure of Interest: None declared.